EFFECTS OF CASH, ACCOUNTS RECEIVABLE AND CORPORATE PAYMENTS ON PROFITABILITY OF DRINKING WATER SUPPLIES - Fitriani, Dini; Nur Izzati; Puja Lestari, Putri (Universitas Pasundan, 2024)
This study aims to find out how cash turnover, receivables, and furniture affect the profitability of the Gapura Tirta Rahayu Purwakarta Regional Public Company for Drinking Water from 2016 to 2021. The profitability reflected in ROA is one of the independent variables in this study, and the dependent variables are cash turnover, billing, and inventory. The causal associative method is used in this quantitative research. This study uses purposive sampling and secondary data. Meanwhile, the data was analyzed using SPPS Version 26, descriptive statistics, multiple linear regression, t-test, f-test, and determination coefficient analysis. The results showed that only one component affected profitability inventory turnover. Profitability is partly influenced by cash and debit turnover. The results of the f test showed that the significance value was 0.035, which was below 0.05, and the f value of 27.883 was below the table f 9.28. As a result, the calculation results showed that Ha was accepted. This shows that the turnover of goods, credit and cash affects profitability simultaneously.